Optimizing ChatGPT for scientific writing in the digital age - Pratiwi, Noor Komari; Yulianto, Bambang; Mintowati, Mintowati; Sodiq, Syamsul (LITERA, 2024)
The emergence of advanced artificial intelligence-based machines such as ChatGPT has brought about changes in the scientific writing process, especially among students. Aspects of originality, creativity, and quality of writing results in the scientific writing process need to be studied to maintain academic integrity, open up opportunities for idea development, and produce coherent and structured writing.  This study aims to analyze the use of ChatGPT as a tool in the process of scientific writing in Indonesian, especially in writing the background of the problem for the preparation of the final project of Informatics Engineering study program students. This research is a descriptive qualitative research with content analysis approach. Sampling was done by purposive sampling technique.  Sampling was done by purposive sampling technique. A total of 18 students of class R67 in semester VI of the Informatics Engineering study program, Indraprasta PGRI University Jakarta were selected because they routinely use ChatGPT in working on scientific writing assignments. Data was collected by reviewing documents in the form of the results of the task of writing the background of the problem made by students using ChatGPT as a tool in the Scientific Writing course. The use of ChatGPT in scientific writing offers significant benefits in terms of creativity and writing quality. The results show that this technology can make learning more efficient by creating new concepts and improving understanding of research ideas. In addition, ChatGPT also helps to produce quality writing. However, ethical issues related to academic integrity should be considered by analyzing the originality aspect through similarity check with turnitin application. Therefore, while ChatGPT provides many benefits in improving the academic writing process, it is imperative to balance these benefits with careful attention to ethical considerations to maintain academic integrity.